2012
DOI: 10.1021/ie3013715
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-Graining Approach to Infer Mesoscale Interaction Potentials from Atomistic Interactions for Aggregating Systems

Abstract: A coarse-graining (CG) approach is developed to infer mesoscale interaction potentials in aggregating systems, resulting in an improved potential of mean force for Langevin dynamics (LD) and Brownian dynamics (BD) simulations. Starting from the evolution equation for the solute pair correlation function, this semi-analytical CG approach identifies accurate modeling of the relative acceleration between solute particles in a solvent bath as a reliable route to predicting the time-evolving structural properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…In earlier work [13] it was shown that although molecular dynamics (MD) simulations of aggregation in dilute systems with full solvent interactions are still too computationally expensive, mesoscale methods such as LD with modeled solvent interactions scale favorably to larger systems while retaining the capability of representing structure in aggregating systems. A coarse-graining procedure recently developed in our group to specify the potential of mean force in LD for aggregating systems yields time-evolving structure in nonequilibrium aggregating systems that matches very well with MD simulations in both diffusion-limited and reaction-limited regimes [14]. With this improved potential of mean force, the authors have confidence that LD simulations of aggregation can reliably predict important aggregation statistics such as the extent of aggregation, time-evolving solute pair correlation function, and dynamically scaled cluster size distribution that have been compared with MD simulations of smaller model systems [14].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In earlier work [13] it was shown that although molecular dynamics (MD) simulations of aggregation in dilute systems with full solvent interactions are still too computationally expensive, mesoscale methods such as LD with modeled solvent interactions scale favorably to larger systems while retaining the capability of representing structure in aggregating systems. A coarse-graining procedure recently developed in our group to specify the potential of mean force in LD for aggregating systems yields time-evolving structure in nonequilibrium aggregating systems that matches very well with MD simulations in both diffusion-limited and reaction-limited regimes [14]. With this improved potential of mean force, the authors have confidence that LD simulations of aggregation can reliably predict important aggregation statistics such as the extent of aggregation, time-evolving solute pair correlation function, and dynamically scaled cluster size distribution that have been compared with MD simulations of smaller model systems [14].…”
Section: Introductionmentioning
confidence: 71%
“…A coarse-graining procedure recently developed in our group to specify the potential of mean force in LD for aggregating systems yields time-evolving structure in nonequilibrium aggregating systems that matches very well with MD simulations in both diffusion-limited and reaction-limited regimes [14]. With this improved potential of mean force, the authors have confidence that LD simulations of aggregation can reliably predict important aggregation statistics such as the extent of aggregation, time-evolving solute pair correlation function, and dynamically scaled cluster size distribution that have been compared with MD simulations of smaller model systems [14]. The essential features of this improved LD model that is used to study sheared aggregating systems in this work are described in Sec.…”
Section: Introductionmentioning
confidence: 71%
“…It is shown that the random fluctuation forces arise naturally as an output of the coarse-graining procedure, and, furthermore, can be used with second fluctuation-dissipation theorem to compute the friction tensor components. This procedure for parameterizing the Langevin equation is in contrast to other examples 24,25,28,42,43 where the frictional force is first determined and then used to derive the random fluctuation force. The PDF-based CG approach is tested for water and a dilute glucose solution, and the results show remarkable agreement with the dynamics obtained from reference all-atom simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Equation (2) was originally derived to describe the dynamics of a Brownian particle across time scales 39,40 and it has been successfully used to model the dynamics of many other systems. [41][42][43] Unfortunately, by replacing the complete friction tensor (Eq. (1)) with a diagonal friction tensor, Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Relative acceleration is the key to capturing structure dependent rheology. The relative acceleration based coarse graining approach (Markutsya, 2010;Markutsya et al, 2012) based on transport equation for two-particle density has been successfully used to model the solute interactions in the presence of solvent, leading to accurate prediction of nanoparticle aggregation using Brownian dynamics simulations. The crucial unclosed term that needs to be modeled in the two-particle transport equation is the relative acceleration between two particles conditional on their relative separation and relative velocity.…”
Section: Relative Acceleration Concept For Average Contact Stress Betmentioning
confidence: 99%